2014
DOI: 10.1016/j.chom.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Plays a Key Role in Spatiotemporal Pathogenesis of Cerebral Malaria

Abstract: Cerebral malaria is a complication of Plasmodium falciparum infection characterized by sudden coma, death, or neurodisability. Studies using a mouse model of experimental cerebral malaria (ECM) have indicated that blood-brain barrier disruption and CD8 T cell recruitment contribute to disease, but the spatiotemporal mechanisms are poorly understood. We show by ultra-high-field MRI and multiphoton microscopy that the olfactory bulb is physically and functionally damaged (loss of smell) by Plasmodium parasites d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 55 publications
(69 reference statements)
9
55
0
Order By: Relevance
“…Our results on CD8 + T cell activation confirm previous ex vivo data showing a superior efficiency of CD8 + DC at priming OT-I cells after exposure to transgenic PbA parasites expressing SIINFEKL (9). They are also consistent with in vivo studies showing a reduced number of activated endogenous CD8 + T cells after PbA infection of mice deficient in CD8 + DC (37,38,69). As CD8 + DC possess specialized machinery for cross-presentation (34), this likely underlies their unique capacity to prime CD8 + T cells during infection by Plasmodium species.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results on CD8 + T cell activation confirm previous ex vivo data showing a superior efficiency of CD8 + DC at priming OT-I cells after exposure to transgenic PbA parasites expressing SIINFEKL (9). They are also consistent with in vivo studies showing a reduced number of activated endogenous CD8 + T cells after PbA infection of mice deficient in CD8 + DC (37,38,69). As CD8 + DC possess specialized machinery for cross-presentation (34), this likely underlies their unique capacity to prime CD8 + T cells during infection by Plasmodium species.…”
Section: Discussionsupporting
confidence: 81%
“…Batf3-deficient mice contain all DC subsets except CD8 + DC and their migratory equivalents, the CD103 + DC, and have been shown to sustain low CD8 + T cell proliferation after PbA infection (69). However, on a B6 background, some CD8 + DC can be found in the LN of Batf3-deficient mice (70) and precursors capable of MHC II-restricted presentation but not cross-presentation are found in the spleen (71).…”
Section: Cd8 + DC Are the Main Apc For Pbt-ii Cellsmentioning
confidence: 97%
“…This region is populated with an intricate network of microvessels. Recently, Zhao et al showed that microhemorrhages occur early during ECM in this region (47). Our data corroborate this finding and also show that functionally, these hemorrhages are associated with a leaky BBB.…”
Section: Discussionsupporting
confidence: 81%
“…Neither capillaries nor arterioles in the cortical microvasculature of mice with ECM nor PCV, arterioles, or capillaries of mice with hyperparasitemia were affected (Nacer et al, in press), thus emphasizing the central role of the postcapillary venule BBB in the ECM-associated vasculopathy (Nacer et al, 2012). Similarly, CD8+ T cells were observed to actively crawl along the wall of larger vessels of the olfactory bulb of PbA-infected mice (Zhao et al, 2014). Because leukocyte adhesion occurred in PCV and larger venules, the center of these vessels remained perfused and complete vascular occlusion was not observed.…”
Section: Lessons From the Murine Modelmentioning
confidence: 93%